Upaya Badan Narkotika Nasional Provinsi Bali dalam Menanggulangi Tindak Pidana Penyelundupan Narkotika oleh Warga Negara Asing - Gede Esa Surya Pramana; A.A Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2022)
Narcotics smuggling carried out by foreigners is strictly prohibited in Indonesia, narcotics crime in society shows a tendency to increase narkotika this international crime enemy for country in the word. The National Narcotics Agency (BNN) is the front line in the fight against narcotics crimes, especially in the case of narcotics smuggling by foreigners. This thesis discusses the efforts of the Bali Province National Narcotics Agency in tackling Narcotics smuggling by foreigners and criminal sanctions if foreigners are caught smuggling Narcotics. This study uses an empirical legal research type with a sociological legal approach. The results of this study are the efforts of the Bali Province National Narcotics Agency in tackling Narcotics smuggling by foreigners by carrying out preventive and repressive efforts and criminal sanctions if foreigners are caught smuggling narcotics, namely imprisonment, fines, principal crimes and additional penalties.machine detection devices X-Ray at Ngurah Rai Airport and to foreigners not to try to smuggle narcotics because they contain opiate substances such as cigarettes that endanger themselves and others and if caught smuggling narcotics subject to imprisonment, fines , principal punishment, and additional punishment.